Kontekstualisasi Mufasir Nusantara Dan Timur Tengah Terhadap Kata Syura - Sholihah, Diana Nur; Mursalim; Fansuri, Fuad; Hakim, Muhammad Fathurahman (LPPM IAIN Sorong, 2024)
Deliberation is a form of cohesion and social unity in solving a problem. The Al-Qur'an itself has at least three verses that talk about consideration, using the terms Shura, Tasyawur and Syawir, each of which is contained in Surah Al-Syurah: 38, al-Baqarah: 233 and Ali Imran: 159. Therefore, one of the aims of the authors of this study is to find out what the views of the scholars and religious leaders are regarding meditation and how the verses regarding meditation are explained.This search is research conducted as part of a library research, namely by studying literature related to research. In addition, this study uses theory as an analytical tool, namely descriptive analysis. After examining the interpretations of Quraish Shihab in Al-Misbah and Hamka in the interpretations of Al-Azhar, Wahbah Al-Zuhail, Fakhruddin Alrazi, Sayyid Qutb and Muhammad Abduh according to reasoning, it can be concluded that deliberation is classified as things that are recommended in the Al-Qur’an because there are many benefit in it. As for how negotiations should be carried out, the Qur'an does not explain this in detail. According to Hamka, deliberations are world affairs whose deliberations are based on Maslaha and Mafsadat. Quraish Shihab explained that by not explaining in detail about the deliberations, this allowed the community to negotiate according to the times because it was not explained in detail how the deliberations process was carried out.